2009
DOI: 10.1111/j.1464-410x.2009.08455.x
|View full text |Cite
|
Sign up to set email alerts
|

Penile fractures: immediate surgical approach with a midline ventral incision

Abstract: OBJECTIVES To present our experience with immediate surgical treatment of penile fractures, using a midline ventral incision, as the choice of either immediate surgical or conservative treatment in penile fractures, as well as the type of surgical incision, remains controversial. PATIENTS AND METHODS In a period of 5 years (2002–2006) eight patients were treated in our department for a penile fracture. The diagnosis was established by a history and clinical examination. In six patients ultrasonography before s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 26 publications
(43 reference statements)
0
39
0
1
Order By: Relevance
“…On long term, 6.6% of patients in our series had ED, which is within the range of 0-16.6% previously reported. [13][14][15][16][17][18][19] We preferred the sub-coronal circumferential incision because of the excellent exposure of the three corpora, which avoids accidental missing of a urethral injury or multiple injuries of the tunica. 26 The right side was commonly affected (56.1%) in agreement with many reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On long term, 6.6% of patients in our series had ED, which is within the range of 0-16.6% previously reported. [13][14][15][16][17][18][19] We preferred the sub-coronal circumferential incision because of the excellent exposure of the three corpora, which avoids accidental missing of a urethral injury or multiple injuries of the tunica. 26 The right side was commonly affected (56.1%) in agreement with many reports.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Contemporary series showed that the incidence of ED after surgical repair of fracture penis ranges from 0% up to 16.6%. 6,7,[13][14][15][16][17][18][19] Several important issues may be raised during discussing the development of ED after surgical repair of fracture penis. First, is delayed presentation after trauma a risk factor for ED?…”
Section: Introductionmentioning
confidence: 99%
“…While the tunica albuginea thickness of penis is about 2 mm in the flaccid state, the thickness decreases about 0.25 to 0.5 mm during penile erection [1]. The most common cause of penile fracture are traumas during sexual intercourse in patient's history [2]. Less often causes are the penis with hands is forced into flexion, the erected penis bended during sleep and falling out of bed [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of penile fracture are traumas during sexual intercourse in patient's history [2]. Less often causes are the penis with hands is forced into flexion, the erected penis bended during sleep and falling out of bed [2][3][4][5]. Physical examination is usually sufficient for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation